Indonesian Islam during the reign of colonialism (1600-1942): An historical account of challenges and responses towards the Dutch policies = Islam Indonesia di zaman penjajahan (1600-1942): cabaran dan tindak balas terhadap dasar Belanda - Ahmad, Nadzrah (International Islamic University Malaysia, 2019)
Indonesian Islam was marked by a long history of struggles between the three centuries Colonialization power and the responses of the Muslims to emerge above the socio-political challenges towards reclaiming their identity. During the three hundred years of its ruling, the Dutch attempted its best to gain not only political power over the economic produce of the country but also to win supports and admiration by the public. Along these attempts the Colonial power implemented strategies by means of culture and the adatlaw and other forms of national policies in order to tone down the newly found voice of Reformism reverberated by the Middle Eastern prominent mufassir Muhammad Abduh. Muhammadiyah and Nahdatul Ulama became the platforms between Traditionalists and Modernists Islam of Indonesia. This paper attempts to assess the extent of Colonial involvement in giving the Indonesian Islam its identity together with responses exhibited by the Muslims towards the these challenges. Historical accounts of Islam in Indonesia shall be examined from year 1600 until 1942.